Penerapan Digital Marketing Dalam Meningkatkan Penjualan Produk Fabil Natural - Evva Ari Nur Viddiastuti; Jeanny Pricilia Anneke Winowatan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
In this millennial era, skincare has become a priority need that must be met by women and men, various skincare brands have emerged from within and outside the country, making competition even tighter. Marketing via internet media has also developed rapidly. This makes digital marketing the key to marketing because a passive promotional system can help business and expand the market. The purpose of this research is to find out how Fabil Natural's strategy is in implementing digital marketing and how the use of this strategy has an impact on Fabil Natural's sales. This research uses qualitative methods with interview, observation and documentation techniques. The research results show that the application of digital marketing is carried out by utilizing websites, blogs and social media including Instagram, Tiktok, Youtube and WhatsApp Business to post products and share content, as well as using the Shopee and Tokopedia websites and marketplaces as a place for easy, safe buying and selling transactions. and fast. Even though there are several obstacles, digital implementation has a positive impact in increasing product sales.